2017
DOI: 10.3390/beverages3010017
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea and Its Extracts in Cancer Prevention and Treatment

Abstract: Green tea (GT) and green tea extracts (GTE) have been postulated to decrease cancer incidence. In vitro results indicate a possible effect; however, epidemiological data do not support cancer chemoprevention. We have performed a PubMED literature search for green tea consumption and the correlation to the common tumor types lung, colorectal, breast, prostate, esophageal and gastric cancer, with cohorts from both Western and Asian countries. We additionally included selected mechanistical studies for a possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 253 publications
(341 reference statements)
0
12
0
Order By: Relevance
“…The control of catechins under intracellular pool of nitro-oxidative stress is mainly responsible for their anticancer properties [33]. Therefore, polyphenolic compounds that bring health-promoting properties for the body can also result in the opposite effects if very high doses of catechins are used [19]. The result is induction of pro-oxidative stress, as well as oxygen damage to cellular components.…”
Section: Catechins: Modes Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…The control of catechins under intracellular pool of nitro-oxidative stress is mainly responsible for their anticancer properties [33]. Therefore, polyphenolic compounds that bring health-promoting properties for the body can also result in the opposite effects if very high doses of catechins are used [19]. The result is induction of pro-oxidative stress, as well as oxygen damage to cellular components.…”
Section: Catechins: Modes Of Actionmentioning
confidence: 99%
“…However, it is worth taking into consideration the oxidative potential of catechins, for example, when using green tea in the form of dietary supplements, as a result of which there is a possibility for the formation of very highly reactive metabolites with quinone structure. Quinones, as a result of redox reactions, have also the potential to generate high amounts of reactive oxygen species [19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our study, this meta‐analysis found inconsistent results among reports with different study designs. A more recent systematic review concluded that the longevity of GT consumers is probably due to other factors like genetic or lifestyle factors (Schulze et al, ). Although a higher number of studies was included in our review, as compared with that published by Ogunleye et al (), heterogeneity was present in results, which were mainly due to various data collection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between lifestyle‐related parameters and breast cancer risk has been studied and some of them like breastfeeding, body fat, and adult attained height reached a “convincing” level but evidence indicating a relationship between some foods and breast cancer risk remains insufficient (Li et al, ). The lower rates of breast cancer in the Asian population who consume high levels of green tea (GT), has made the scientists to suggest a protective effect for GT against breast cancer (Schulze, Melzer, Smith, & Teschke, ), but the results of published epidemiological studies, which have evaluated the possible chemopreventive effects of GT in humans, are inconsistent (Inoue et al, ; Nagano, Kono, Preston, & Mabuchi, ; Shrubsole et al, ; Suzuki et al, ; Zhang, Holman, Huang, & Xie, ). Besides, it seems that GT extracts may be even hepatotoxic (Teschke, Zhang, Melzer, Schulze, & Eickhoff, ).…”
Section: Introductionmentioning
confidence: 99%
“…prevention of human cancer at organs other than the liver, usually with disappointing results; for a limited number of tumors, a marginal preventive effect by catechins was observed in subgroups of patients (14). Study publications often were of low quality and difficult to interpret; this has also been discussed by Huang et al (1) for their meta-analysis, which is heavily influenced by one study contributing half of all cases.…”
mentioning
confidence: 99%